Identification of Limitations in the Implementation of Process Approach in SMEs in the Republic of Serbia - Radosavljević, Marija; Dreković, Edisa (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Companies that are focused on quality and see it as a way to provide a competitive advantage, and apply ISO 9001 standard in their business, claim that process approach is indispensable. The ISO 9001:2008 standard explicitly states that process orientation is mandatory, because process is constant and the company’s business is changeable. Reasons for standardization usually include: improving the company’s image, meeting customer requirements, improving products and services, achieving strategic goals, achieving business excellence. According to the latest ISO report from September 2020, at the global level, in a period of 10 years, there is a decreasing trend in number of issued certificates, especially when it comes to small and medium enterprises (SMEs). The aim of the research is to identify the limitations of process approach adoption in SMEs in Serbia, based on the theoretical generalizations of previously conducted research, but also results of empirical research. Since it is assumed that companies that have implemented the ISO standard system, by definition, nurture a process approach, the research was conducted on a sample of SMEs that are certified. Methods of statistical analysis (correlation and regression analysis, factor analysis) were used to test the hypotheses. Preliminary results show that most of the constraints stem from inadequate human resource management. The lack of employees’ empowerment and their resistance stand out as the dominant barriers.